Innovative approaches to increasing the efficiency of natural resource use in the sustainable development of our country’s economy - Khamraeva Sayyora Nasimovna; Khojanova Gulshoda Otamurodovna (THE INNOVATION ECONOMY, 2026)
This article reveals the current state of increasing the efficiency of natural resource use in the sustainable development of the economy of Uzbekistan, scientifically substantiates the importance of innovative approaches. The article analyzes strategies for the efficient use of resources through IoT technologies, renewable energy sources, geoinformation systems, and digitalization tools